2003
DOI: 10.1002/uog.138
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anxiety and fetal behavior at 15 weeks' gestation

Abstract: Objective To analyze the relationship between maternal anxiety and fetal behavior at 15 weeks' gestation. Methods Conclusions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
0
17
2
Order By: Relevance
“…To date, studies have demonstrated that anxiety levels before prenatal diagnostic procedures are higher in amniocentesis than in ultrasound [8][9][10]37 or control groups. 38 In contrast, the findings of the current study indicate that women undergoing amniocentesis or ultrasound experience similar levels of anxiety prior to the procedure. Also, anxiety in both groups were significantly higher than in the general female population, 26 suggesting that ultrasound, despite being a noninvasive procedure, does induce a substantial level of anxiety in pregnant women.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…To date, studies have demonstrated that anxiety levels before prenatal diagnostic procedures are higher in amniocentesis than in ultrasound [8][9][10]37 or control groups. 38 In contrast, the findings of the current study indicate that women undergoing amniocentesis or ultrasound experience similar levels of anxiety prior to the procedure. Also, anxiety in both groups were significantly higher than in the general female population, 26 suggesting that ultrasound, despite being a noninvasive procedure, does induce a substantial level of anxiety in pregnant women.…”
Section: Discussioncontrasting
confidence: 83%
“…To date, studies have demonstrated that anxiety levels before prenatal diagnostic procedures are higher in amniocentesis than in ultrasound or control groups . In contrast, the findings of the current study indicate that women undergoing amniocentesis or ultrasound experience similar levels of anxiety prior to the procedure.…”
Section: Discussioncontrasting
confidence: 80%
“…The major limitations of the present study were related to the small size of the sub-sample involved in the assessment of fetal behavior and to the small period of 3 min for observation of motor activity, when compared to previous studies developed in this domain [59,91]. These limitations resulted from institutional constraints to the implementation of the present research which imposed the assessment of fetal movements by the obstetrician during the morphological ultrasound routine.…”
Section: Discussionmentioning
confidence: 78%
“…Several others did not find this effect, neither for fetal growth [56][57][58] nor for fetal behavior [59]. DiPietro et al [60] suggest that mild to moderate levels of psychological distress may enhance fetal maturation in healthy populations, as higher levels of prenatal anxiety, non-specific stress, and depressive symptoms can be associated to greater motor and mental development in children at age two.…”
Section: Introductionmentioning
confidence: 96%
“…The first study was conducted at 15 weeks gestation on a small sample ( n = 20) using a 40-minute observation period but found no association (Bartha, Martinez-del-Fresno, Romero-Carmosa, Hunter, & Comino-Delgado, 2003). In the second, maternal cortisol explained 12% of the variability in fetal motor activity observed during a 5-minute ultrasound observation between 20 and 28 weeks gestation (Field, Diego, Hernandez-Reif, Gil, & Vera, 2005).…”
mentioning
confidence: 99%